From the ghetto to the Gulag, from the ghetto to Israel: Soviet collaboration trials against the Shargorod ghetto’s Jewish Council - Schneider, Wolfgang (Journal of modern European history, 2019)
Beginning in 1944, Soviet authorities arrested former Jewish Council members of different ghettos and put them on trial for collaboration with the Axis powers. This case study examines the 1944 trials of Meir Teich and Isaak Sherf, two leading figures of the Shargorod ghetto’s Jewish administration. Drawing on trial documents, oral history interviews and memoirs, this article focuses on two aspects: how Soviet courts selectively accepted support for the partisans as mitigating circumstances, and how survivor networks among the witnesses influenced the trials. These aspects are discussed in the context of the (re-)Sovietization of formerly occupied territories, in this case Transnistria, the Romanian occupation zone.